2014
DOI: 10.1155/2014/148184
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticles: Green Synthesis, Characterization, and Their Usage in Determination of Mercury Contamination in Seafoods

Abstract: We demonstrate that silver nanoparticles undergo an interaction with Hg 2+ found in traces. The PEG-PVP-stabilized Ag nanoparticles were successfully synthesized via a reduction approach and characterized with surface plasmon resonance UV/Vis spectroscopy. By utilizing the redox reaction between Ag nanoparticles and Hg 2+ , and the resulted decrease in UV/Vis signal, we develop a colorimetric method for detection of Hg 2+ ion. A linear and inversely proportional relationship was found between the absorbance in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…To overcome these limitations and to avoid complicated instrumentation, several methods based on colorimetry and probes of noble metals have been developed for the easy detection of Hg 2+ . (18,20,21,29,30) In this study, the one-pot, simple, and rapid green synthesis of highly stable and colloidal AgNPs has been achieved using Panax ginseng root extract as a reducing and capping agent. The synthesized AgNPs were investigated for their structural and functional properties and used as a material for the detection of Hg 2+ based on the dissolution of AgNPs and the formation of Ag-Hg amalgam.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these limitations and to avoid complicated instrumentation, several methods based on colorimetry and probes of noble metals have been developed for the easy detection of Hg 2+ . (18,20,21,29,30) In this study, the one-pot, simple, and rapid green synthesis of highly stable and colloidal AgNPs has been achieved using Panax ginseng root extract as a reducing and capping agent. The synthesized AgNPs were investigated for their structural and functional properties and used as a material for the detection of Hg 2+ based on the dissolution of AgNPs and the formation of Ag-Hg amalgam.…”
Section: Introductionmentioning
confidence: 99%
“…In order to provide the full evidence with respect to the AgNPs presence, Figures 2(e) and 2(f) show the UV-Vis analysis corresponding to the CO and Ih samples, respectively. In these spectra, typical bands around 400 nm are observed in both cases [12,41]. Specifically, for AgNPs-NaBH 4 and AgNPs-EG samples, bands located at 419 and 388 nm were observed, respectively.…”
Section: Uv-vis Spectroscopymentioning
confidence: 81%
“…30,33 Ahmed et al observed the sensitivity of AgNPs toward Hg 2+ which was identied by UV-vis absorption spectra. 34 Since the standard electrode potential of Ag + /Ag is 0.80 V and Hg 2+ /Hg is 0.85 V, it is expected that a redox reaction can occur between zerovalent silver and Hg 2+ .…”
Section: Optimization Of Agnp Usa Mdspe Conditionsmentioning
confidence: 99%